5(2x-2)=3(4-2x)

Simple and best practice solution for 5(2x-2)=3(4-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-2)=3(4-2x) equation:


5(2x-2)=3(4-2x)

We simplify the equation to the form, which is simple to understand
5(2x-2)=3(4-2x)

Reorder the terms in parentheses
+(+10x-10)=3*(4-2x)

Remove unnecessary parentheses
+10x-10=+3+*(+4-2x+)

Reorder the terms in parentheses
+10x-10=+(+12-6x)

Remove unnecessary parentheses
+10x-10=+12-6x

We move all terms containing x to the left and all other terms to the right.
+10x+6x=+12+10

We simplify left and right side of the equation.
+16x=+22

We divide both sides of the equation by 16 to get x.
x=1.375

See similar equations:

| -2-5n=-5n^2 | | 3x+9/15=6 | | 8x^2+8xy-20y=0 | | -x+9=1/3(-9x+6)+1 | | -3(3r+3)=5-7r | | 5x-1-4x=x+17 | | 16-7*2= | | N^2+6=5N | | -3n+9+8n=7n-8n-9 | | 12x+2=4x-22 | | n+7/4=7/20 | | 5x=5/8 | | (4y-1)+(2x+5)=180 | | 6n-2=6n-7 | | 6w^2+24w-72=0 | | A^2-3A-3=5 | | 2x-16-x=x-16 | | 5x^2+24=0 | | 3y^2+51y+90=0 | | 3x=24*0.5 | | 3x+9/15=16 | | 8-9x=80 | | -x^2=36 | | -6x-10=-4x-14 | | 2x-21-x=x-21 | | 3xx-1=x+4 | | -9x-8=x-48 | | 37=5-x+3x | | -4/3t=-16 | | 3x?-1=x+4 | | 5y^2-45y+70=0 | | 17x-3=8x |

Equations solver categories